Comparison between the Lineament Trends at Western Euphrates River and Eastern Parts in Central Iraq, Depending on the Total Horizontal Derivative of Residual Magnetic Maps Obtained from Four Upward Continuation Levels - Majeed, Hayder H.; Al-Banna, Ahmed S. (Iraqi Journal of Science, 2024)
The upward continuation was used to obtain the residual RTP magnetic maps at elevations 2, 12, 16 and 22 km. These maps are processed by the Total Horizontal Derivative (THD) technique to detect the main lineaments that represent the boundary of subsurface sources or fractures. The high background of THD in the central part of the study area supports the presence of a group of faults between the western and eastern parts of the area. The obtained lineaments trends were represented on the rose diagram, as were the main trends in the study area. The predominant lineaments (faults) trends in the western part in descending are N55W, N35W, N05W, N65W, N45W, N25W, N05E, N15E, and N35E, respectively, for the four considered upward elevations. The lineament in eastern part found trending N55W, N35W, N35E, N45W, N45E, N05E, N25E, and N05W, respectively. The lineaments of the western and eastern parts indicate that the main trend in shallow sources is NW-SE, which coincides with the Najd fault system (540-620 Ma) in the Arabian Plate. The deep-level lineaments are trending N-S, which coincides with the Nabitah fault system (680-640 Ma).